RISK OF COVID-19 INFECTION IN PATIENTS WITH MULTIPLE SCLEROSIS TREATED WITH OCRELIZUMAB – A SINGLE CENTER EXPERIENCE - Todorović, Stefan (Acta medicae Medianae, 2023)
Ocrelizumab is a disease-modifying therapy (DMT) for active relapsing and early primary progressive multiple sclerosis (MS). During the COVID-19 pandemic, it was speculated that ocrelizumab might increase the risk of COVID-19 in patients with MS. The aim was to assess the risk of COVID-19 infection in MS patients treated with ocrelizumab. Our study included patients who met revised McDonald criteria and who were treated with ocrelizumab at the University Clinical Centre Niš. The diagnosis of COVID-19 was made by positive PCR (polymerase chain reaction) or antigen test. The severity of the disease was estimated based on the Australian guidelines for the clinical care of people with COVID-19. Out of 103 patients treated with ocrelizumab, 33 (32%) were found to be infected with COVID-19. Out of these, there were 10 (30.3 %) COVID-positive men and 23 (69.7%) women. The average age of affected patients was 43.9±9.1. Most of them had mild clinical presentation of COVID-19 infection (81.8%), 12.1% had moderate clinical presentation, 3% with severe clinical manifestation and one patient died. There was no significant impact of ocrelizumab administration in patients with MS on the increased risk of COVID-19 infection and the development of severe clinical manifestations of the disease. In our cohort, patients with moderate and severe COVID-19 disease were usually older than 50 (66.7%), although there were not many of those patients.